Peningkatan Keaktifan dan Hasil Belajar Siswa Menggunakan Media Kancing Genetika - Rikawati (Pencerah, 2022)
The purpose of this study was to determine the effect of using genetic button media in increasing student activity and learning outcomes in Mendel's law. Learning media are materials, tools, and methods/techniques used in teaching and learning activities so that the process of educative communication interaction between teachers and students can take place effectively. This study uses qualitative methods obtained from observations of student activity in the teaching and learning process and quantitative methods obtained from students’ pre-test and post-test results. The results showed an increase in student activity from 41% to 75% and an increase in the percentage of students who obtained a complete score from 50% to 75%.